B-Vitamins and Choline in Human Milk Are Not Impacted by a Preconception Lipid-Based Nutrient Supplement, but Differ Among Three Low-to-Middle Income Settings—Findings From the Women First Trial - Young, Bridget E.; Westcott, Jamie; Kemp, Jennifer; Allen, Lindsay; Hampel, Daniela; Garcés, Ana L.; Figueroa, Lester; Goudar, Shivaprasad S.; Dhaded, Sangappa M.; Somannavar, Manjunath; Saleem, Sarah; Ali, Sumera Aziz; et al. (Frontiers in Nutrition, 2021)
Introduction: Optimal human milk (HM) B-vitamin concentrations remain undefined, especially in areas where undernutrition is prevalent. The impact of supplementation pre-conception through pregnancy on HM B-vitamin composition remains unknown. Methods: HM was collected at 2-weeks postpartum from 200 women in Guatemala, India and Pakistan (the Women First Trial). Women were randomized to start a lipid-based nutrient supplement prior to conception, at end of first trimester, or not at all; intervention continued until delivery. HM concentrations of eight B-vitamins and choline were assessed via ultra-performance liquid chromatography – tandem mass spectrometry. Maternal diet was assessed in early pregnancy, and infant growth followed through six months post-delivery. Results: Despite supplement exposure averaging 15.7 (pre-conception arm) and 6.0 months (prenatal arm), HM B-vitamins did not differ between arms, but site differences were evident. Guatemala had higher HM concentrations of vitamin B3 than Pakistan and India. Pakistan had higher HM concentrations of thiamin and vitamin B6 than India and Guatemala. Cohort average HM vitamin B2 (162±79 µg/L) and B6 (31.8±24.6 µg/L) fell below values defined as deficient in 81.5% and 85.5% of samples, potentially reflecting sampling procedures and timing. Maternal dietary intakes of only vitamin B6 and choline were associated with the corresponding concentrations in HM (p<0.005). No HM B-vitamin concentrations were associated with infant growth. Conclusion: Prenatal supplementation for at least 6 months had no impact on HM B-vitamin concentrations at 2-weeks postpartum. Results suggest that the adequacy of HM composition was generally maintained, with potential exceptions of vitamin B2 and B6.